GLOBAL CLIMATE CHANGE SCALE (GCCS): DEVELOPMENT AND VALIDATION - Yilmaz, Veysel (Journal of Fundamental and Applied Sciences, 2022)
Global Climate Change (GCC) is the increase in global temperature and the change in average climate values. The climate change becoming an 'emergency' that cannot be ignored anymore is called the climate crisis. There is also a need for reliable and validated scales to measure attitudes towards GCC. This study focused on university students' global climate change scale (GCCS) development and validation. In the study, a four-factor scale, called Knowledge, Awareness, Perceived Risk and Responsibility, with an explained variance of 74.51%, was developed. In addition, the general index showing the positive attitude level of high index values towards GCC was 78%, and the index values of Knowledge, Awareness, Perceived Risk and Responsibility dimensions were calculated as 0.76, 0.83, 0.83 and 0.69, respectively.